Innovative approaches to boost mesenchymal stem cells efficacy in myocardial infarction therapy - Chuanfeng An; Yuan Zhao; Lipeng Guo; Zhijian Zhang; Chunxiao Yan; Shiying Zhang; Yujie Zhang; Fei Shao; Yuanyuan Qi; Xun wang; Huanan Wang; Lijun Zhang (Materials Today Bio)
Stem cell-based therapy has emerged as a promising approach for heart repair, potentially regenerating damaged heart tissue and improving outcomes for patients with heart disease. However, the efficacy of stem cell-based therapies remains limited by several challenges, including poor cell survival, low retention rates, poor integration, and limited functional outcomes. This article reviews current enhancement strategies to optimize mesenchymal stem cell therapy for cardiac repair. Key approaches include optimizing cell delivery methods, enhancing cell engraftment, promoting cell functions through genetic and molecular modifications, enhancing the paracrine effects of stem cells, and leveraging biomaterials and tissue engineering techniques. By focusing on these enhancement techniques, the paper highlights innovative approaches that can potentially transform stem cell therapy into a more viable and effective treatment option for cardiac repair. The ongoing research and technological advancements continue to push the boundaries, hoping to make stem cell therapy a mainstream treatment for heart disease.